Optimization Scheduling of Hydro-Wind-Solar Complementary Systems Based on Standby Flow - FANG Guo-hua, LIU Chang, DING Zi-yu (长江科学院院报)
With the access of large-scale wind power stations and solar power stations, wind energy and solar energy affect the safe and stable operation of the power system due to the lack of prediction accuracy. This paper presents an optimal scheduling method for the hydro-wind-solar complementary system based on standby flow. First, the standby flow is set according to the available water of each hydropower station based on the inflow. Then, the optimal scheduling model based on standby flow is developed. The objectives of this model are to maximize power generation and minimize the variance of residual load. Standby flow serves to mitigate the impact of inaccurate wind and solar energy predictions. Finally, a case study is conducted on the cascade hydropower station and connected wind and solar power stations along the lower Yalong River. Results show that compared with the scenario without standby flow, the power generation efficiency of the multi-energy complementary system with standby flow in typical wet month (June) and typical dry month (December) increases by 0.08% and 1.97%, respectively; and the variance of residual load decreases by more than 40%. In conclusion, setting standby flow can balance the power supply and demand of the power system while ensuring power generation efficiency, thereby guaranteeing the safe and stable operation of the power system.